Walking with Legends : Barry Martyn's New Orleans Jazz Odyssey - Martyn, Barry, 1941- (Book collections on Project MUSE., 2007)
Drummer, record producer, bandleader, jazz researcher, and cigar-chomping raconteur Barry Martyn is a New Orleans original who happens to have been born in England. Implausible though this may seem, it makes perfect sense to members of the New Orleans traditional jazz community, who view themselves as an extended family based on merit as much as nativity. For more than forty years, Martyn has been a fixture in the Crescent City's jazz scene, laying down the beat for generations of celebrated musicians and avidly promoting the city's unique musical heritage around the world. In Walking with Leg.